MYO5A Frameshift Variant in a Miniature Dachshund with Coat Color Dilution and Neurological Defects Resembling Human Griscelli Syndrome Type 1 - Matthias Christen; Madeleine de le Roi; Vidhya Jagannathan; Kathrin Becker; Tosso Leeb (Genes, 2021)
A 1-month-old, female, smooth-haired miniature Dachshund with dilute color and neurological defects was investigated. The aim of this study was to characterize the clinical signs, histopathological changes and underlying genetic defect. The puppy had visible coat color dilution and was unable to hold its head on its own or to remain in a stable prone position for an extended period. Histopathological examination revealed an accumulation of clumped melanin and deposition of accumulated keratin within the hair follicles, accompanied by dermal pigmentary incontinence. These dermatological changes were compatible with the histopathology described in dogs with an MLPH-related dilute coat color. We sequenced the genome of the affected dog and compared the data to 795 control genomes. MYO5A, coding for myosin VA, was investigated as the top functional candidate gene. This search revealed a private homozygous frameshift variant in MYO5A, XM_022412522.1:c.4973_4974insA, predicted to truncate 269 amino acids (13.8%) of the wild type myosin VA protein, XP_022268230.1:p.(Asn1658Lysfs*28). The genotypes of the index family showed the expected co-segregation with the phenotype and the mutant allele was absent from 142 additionally genotyped, unrelated Dachshund dogs. MYO5A loss of function variants cause Griscelli type 1 syndrome in humans, lavender foal in horses and the phenotype of the dilute mouse mutant. Based on the available data, together with current knowledge on other species, we propose the identified MYO5A frameshift insertion as a candidate causative variant for the observed dermatological and neurological signs in the investigated dog.